PELATIHAN IMPLEMENTASI K3 DI SMPN 1 MUARA GEMBONG BEKASI - Ja’far Amiruddin; Fransisca Maria F; Catur SK; Himawan HS; Pratomo S; M. Naufal W. (Prosiding Seminar Nasional Pengabdian Kepada Masyarakat, 2023)
Abstract The State Junio High School (SMPN) 1 Muara Gembong Bekasi is currently not optimally running the Occupational Safety and Health (K3) program. So far, the OSH program has put more emphasis on slogans and posting information about OSH. School residents, namely: teachers, education staff, and students at SMPN 1 Muara Gembong not many understand the importance of K3 in schools. Whereas the K3 program in schools is very important and needs special attention, because: 1) Activities in schools need to ensure safety and health aspects for school residents, 2) K3 in schools can be a vehicle for building OSH awareness and culture for the younger generation who are the workforce. productive. The purpose of Community Service Activities (P2M) at SMAN 1 Muara Gembong Bekasi is to improve the performance of K3 implementation at SMPN 1 Muara Gembong Bekasi. This K3 implementation training focused on safety awareness, emergency response in schools, and fire prevention. Through this activity, it is hoped that there will be an increase in K3 at SMPN Muara Gembong Bekasi related to: awareness, knowledge, and implementation/implementation of K3 by school residents. This P2M activity is also a manifestation of the tridarma of higher education to provide OHS information and education to the public, especially schools. The activity begins with pre-training, in the form of visits to schools to see the conditions and identify the needs of SMPN 1 Muara Gembong. Information and data were obtained through observation and interviews with school leaders, teacher representatives, student representatives and education staff representatives. The training activity was carried out in August 2022 at SMPN 1 Muara Gembong. This P2M activity also involved students from the Fire Safety Engineering Study Program. Abstrak Sekolah Menengah Pertama Negeri (SMPN) 1 Muara Gembong Bekasi saat ini belum optimal menjalankan program Keselamatan dan Kesehatan Kerja (K3). Program K3 sejauh ini lebih ditekankan pada slogan dan pemasangan informasi tentang K3. Warga sekolah yakni: guru, tenaga kependidikan, dan siswa di SMPN 1 Muara Gembong belum banyak yang memahami pentingnya K3 di sekolah. Padahal program K3 di sekolah sangat penting dan perlu perhatian khusus, karena: 1) Aktifias di sekolah perlu dipastikan aspek keselamatan dan kesehatan bagi warga sekolah, 2) K3 di sekolah dapat menjadi wahana untuk membangun kesadaran dan budaya K3 bagi generasi muda yang merupakan angkatan kerja produktif. Tujuan Kegiatan Pengabdian kepada Masyarakat (P2M) di SMPN 1 Muara Gembong Bekasi adalah untuk meningkatkan kinerja implementasi K3 di SMPN 1 Muara Gembong Bekasi. Pelatihan implementasi K3 ini difokuskan pada safety awareness, penanggulangan keadaan darurat di sekolah, serta pencegahan kebakaran. Melalui kegiatan ini diharapkan ada peningkatan K3 di SMPN Muara Gembong Bekasi terkait: kesadaran, pengetahuan, dan pelaksanaan/ implementasi K3 oleh warga sekolah. Kegiatan P2M ini juga salah satu wujud dari tridarma perguruan tinggi untuk memberikan informasi dan edukasi K3 ke masyarakat, khususnya sekolah. Kegiatan diawali dengan pra pelatihan, berupa kuunjungan ke sekolah untuk melihat kondisi dan identifikasi kebutuhan SMPN 1 Muara Gembong. Informasi dan data diperoleh melalui observasi dan wawancara dengan pimpinan sekolah, perwakilan guru, perwakilan siswa dan perwakilan tenaga kependidikan. Kegiatan pelatihan dilakukan pada Agustus 2023 di SMPN 1 Muara Gembong. Kegiatan P2M ini juga melibatkan para mahasiswa dari Program Studi Rekayasa Keselamatan Kebakaran.